Effect of the vocal tract filtering on the measurement of vocal cycle perturbations. Issue 18 (1st July 2020) - Bennane, Y.; Kacha, A.
Abstract : Jitter and shimmer appear as symptoms of disordered voices and they are defined as the cycle‐to‐cycle variation of the cycle length and cycle amplitude, respectively. The frequency modulation of the phonatory excitation, i.e. vocal jitter, causes amplitude modulation (shimmer) of the speech signal due to the action of the vocal tract transfer function. In this Letter, the authors investigate the extent to which the vocal tract filtering affects the accuracy of measurement of vocal cycle perturbations of the phonatory excitation. To achieve this goal, the direct digital synthesiser is used to generate a series of glottal excitation cycles with the desired amount of vocal perturbations that crosses the vocal tract model to produce a set of 231 stimuli of sustained vowels [a]. Praat is used to measure the amount of perturbations. Results show that the values of the input shimmer inserted in the glottal excitation are smaller than the values measured by Praat. An undesired amount of shimmer is generated in the speech signal when the glottal excitation signal perturbed with jitter crosses through the vocal tract.